Air-Outlet and Step-Number Effects on a Step-like Plenum Battery’s Thermal Management System - Olanrewaju M. Oyewola; Emmanuel T. Idowu; Morakinyo J. Labiran; Michael C. Hatfield; Mebougna L. Drabo (Batteries)
Optimizing the control of the battery temperature (<semantics>Tb</semantics>), while minimizing the pressure drop (<semantics>∆P</semantics>) in air-cooled thermal management systems (TMSs), is an indispensable target for researchers. The Z-type battery thermal management system’s (BTMS’s) structure is one of the widely investigated air-cooled TMSs. Several designs of air-cooled BTMSs are often associated with the drawback of a rise in <semantics>∆P</semantics>, consequently resulting in an increase in pumping costs. In this study, the investigation of a Step-like plenum design was extended by exploring one and two outlets to determine possible decreases in the maximum battery temperature (<semantics>Tmax</semantics>), maximum battery temperature difference (<semantics>∆Tmax</semantics>), and pressure drop (<semantics>∆P</semantics>). The computational fluid dynamics (CFD) method was employed to predict the performances of different designs. The designs combine Step-like plenum and two outlets, with the outlets located at different points on the BTMS. The results from the study revealed that using a one-outlet design, combined with a Step-like plenum design, reduced <semantics>Tmax</semantics> by 3.52 K when compared with that of the original Z-type system. For another design with two outlets and the same Step-like plenum design, a reduction in <semantics>Tmax</semantics> by 3.45 K was achieved. For <semantics>∆Tmax</semantics>, the use of a two-outlet design and a Step-like plenum design achieved a reduction of 6.34 K. Considering the <semantics>∆P</semantics> performance, the best- and poorest-performing designs with two outlets reduced <semantics>∆P</semantics> by 5.91 Pa and 3.66 Pa, respectively, when compared with that of the original Z-type design. The performances of the designs in this study clearly show the potential of two-outlet designs in reducing <semantics>∆P</semantics> in systems. This study, therefore, concludes that the operational cost of the Step-like plenum Z-type BTMS can be reduced through the careful positioning of the two-outlet section, which will promote the design and development of current and future electric vehicle (EV) technologies.